BLASKI I CIENIE BADAŃ POSTKOLONIALNYCH NAD POLSKĄ LITERATURĄ ROMANTYCZNĄ - Bagłajewski , Arkadiusz (Studia Europaea Gnesnensia, 2017)
This paper aims at a synthetic presentation of four representative research practices in the first stage of postcolonial studies concerned with Polish literature of the Romantic period. This is currently one of the key tools utilised in the studies of Polish Romanticism, which proved to offer a considerable scope for revisions, especially with regard to the myth of the Borderlands and Messianism, thus enabling major Romantic ideologies and myths to be redefined in terms of identity. An analysis of research discourses reveals the shortcomings and benefits of the postcolonial method when employed in the studies of Polish Romanticism. On the one hand, an all too rigid application of the tools has led to certain interpretive simplifications of Romantic texts, while on the other the authors of the discussed works were able to conceptualize the identities of Polish Romantic literature anew.